Tolkien and the study of his sources critical essays - Fisher, Jason, 1970- (McFarland & Co., 2011)
"This compendium by leading Tolkien scholars describes the theory and methodology for proper source criticism of Tolkien's works and then provides practical demonstrations of the approach. Ranging widely across Tolkien's writings, as well as across the periods and genres from which he took inspiration, the essays provide the most balanced and comprehensive demonstration of Tolkien source criticism available"--Provided by publisher.